Singin' the blues - Miglis, Jenny; Marantz, Larissa; DiPaolo, Katharine (New York: Simon Spotlight/Nickelodeon, 2005)
Susie meets a talent agent who promises to make her a pop star.
"Nick All grown up!, #1."
"Based on the TV series Nickelodeon All Grown Up"--T.p. verso.
Keywords: Singing; Talent scouts; Schools; Singing; Talent scouts; Schools